ANALISIS PENGARUH DANA PIHAK KETIGA, SUKU BUNGA KREDIT, NOAN PERFORMING LOAN TERHADAP PEMBERIAN KREDIT BAGI USAHA KECIL DI KOTA AMBON - Roy Seleky (Manis: Jurnal Manajemen dan Bisnis, 2019)
The main source of investment funding in the develomping country like Indonesia commonly depends on Bank Loan for the Micro Scale Business in necessary to increase the productivity of their business.The research has aim to achieve emperical evidence about the influence of Non Performing Loan, Credit rate and Third Parties Fund towards Presenting an Investment Credit Loan to Micro Scale Business in Ambon. The Independent variables in the research are, Third Parties Fund, Credit Rate, and Non Performing Loan ( NPL ). It has used the past year form ( t-1 ) that has been observed since 2010 – 2014, meanwhile the Dependent Variables is Presenting an Investment Credit Loan for Micro Scale Business.The research implemented in Public Bank in Ambon as the research objects ( Data Source : Bank Indonesia of Ambon Branch ) under period of 2010 to 2014. The varibles that has been used in this researchn were amount of Third Parties Fund, Non Performing Loan, and Credit Rate that liquidate by Bank Indonesia of Ambon. The analysis method that has been used in this research are, Linear Regression, testing of assumption and testing the hypothesis.Based on the result of the research, Non Performing Loan has positive influence in Presenting the Investment Loan to Micro Scale Business, and then Credit Rate has a negative influence toward presenting the investment loan to micro scale business, meanwhile third parties fund has a positive influence in presenting the Investment Loan to Micro Scale Businees.